Participation of two general stress response proteins from Xanthomonas citri subsp. citri in environmental stress adaptation and virulence. Issue 8 (8th July 2020) - Barcarolo, María Victoria; Gottig, Natalia; Ottado, Jorgelina; Garavaglia, Betiana S
ABSTRACT: Xanthomonas citri subsp. citri (Xcc) is the bacteria responsible for citrus canker. During its life cycle Xcc is found on leaves as epiphyte, where desiccation conditions may occur. In this work, two Xcc genes, XAC0100 and XAC4007, predicted in silico to be involved in general stress response, were studied under salt, osmotic, desiccation, oxidative and freezing stress, and during plant-pathogen interaction. Expression of XAC0100 and XAC4007 genes was induced under these stress conditions. Disruption of both genes in Xcc caused decreased bacterial culturability under desiccation, freezing, osmotic and oxidative stress. Importantly, the lack of these genes impaired Xcc epiphytic fitness. Both Xac0100 and Xac4007 recombinant proteins showed protective effects on Xanthomonas cells subjected to drought stress. Also, Escherichia coli overexpressing Xac4007 showed a better performance under standard culture, saline and osmotic stress and were more tolerant to freezing and oxidative stress than wild type E. coli . Moreover, both Xac0100 and Xac4007 recombinant proteins were able to prevent the freeze-thaw-induced inactivation of L-Lactate dehydrogenase. In conclusion, Xac0100 and Xac4007 have a relevant role as bacteria and protein protectors; and these proteins are crucial to bacterial pathogens that must face environmental stressful conditions that compromise the accomplishment of the complete virulence process. Abstract : Two general stress response proteins from a plant pathogen involved in environmental stress adaptation and virulence.